Genetic effects and heterosis for seed yield and physio-biochemical traits in chickpea (Cicer arietinum) - CHOUDHARY, REKHA; JAIN, S K; OLA, M P; BHARDWAJ, C (The Indian Journal of Agricultural Sciences, 2023)
A 8-parent diallel analysis was taken to investigate the genetic effects and heterosis for seed yield and 6 physiobiochemical characters in chickpea (Cicer arietinum L.) under timely and late sown conditions at research farm of Rajasthan Agricultural Research Institute, Durgapura, Jaipur, Rajasthan during winter (rabi) seasons of 2020–21 and 2021–22. Significant disproportion of GCA and SCA variances depicted that both additive and non-additive gene action plays a vital role for genetic control of all the traits. Though the relative amount of GCA/SCA was less than unity for all traits under study signifying that non-additive gene plays a key role under the environments studied. The parents CSJ-515, CSJD-884 and RSG-963 emerged as good general combiners for seed yield, additionally the parents CSJ 515 and RSG 963 were considered as good general combiners for CC and PV, whereas parent CSJD-884 for MSI, TCC and PC. The crosses CSJD 884 × RSG 963, CSJD 884 × RSG 973, CSJD 884 × Avrodhi, CSJD 884 × HC 5, RSG 963 × CSJ 515, RSG 974 × HC 5 and CSJ 515 × HC 5 showed consistent SCA effect and heterobeltiosis for seed yield and one or more heat tolerant physio-biochemical traits and projected that these crosses would provide enviable transgressive segregate for heat tolerance.